ASSESSING COMPUTER SKILLS OF INMATES AT BJMP CITY OF NAGA: FOUNDATION FOR AN EXTENSION PROJECT - Glenn A. Trinidad (Chelonian Research Foundation, 2024)
This study evaluates the computer system servicing skills of Persons Deprived of Liberty (PDLs) at the Bureau of Jail Management and Penology (BJMP) in Naga City, Cebu, as the basis for a proposed extension program. Using a descriptive-evaluative research design, the study surveyed 25 PDLs nearing release. The results, analyzed through mean distribution, revealed low proficiency across all assessed competencies. Basic skills, such as hardware assembly and operating system installation, had an average weighted mean of 2.52, while networking tasks scored the lowest with a mean of 1.85. Office productivity software and Google Suite proficiency were similarly low, with means of 2.35 and 2.58, respectively. These findings highlight a substantial skills gap, suggesting the need for targeted ICT training. The proposed extension program should focus on practical skill development, software proficiency training, and certification to enhance PDLs’ employability and support their reintegration into society. Addressing these skill deficiencies is crucial for reducing recidivism and increasing post-release opportunities for PDLs.